A tisztességes eljáráshoz való jog az Emberi Jogok Európai Bírósága Magyarországgal kapcsolatos gyakorlatában, különös tekintettel az ésszerű határidő követelményére - Nagy, Anita (Debreceni Jogi Műhely, 2020)
As for the right to a fair trial sanctioned by the convention, our most determining deficiencies arise regarding the compliance with a reasonable period of time. Despite of the relatively small number of the Hungarian infringements of the European Convention on Human Rights, the expectation of sufficiently efficient dispositions eliminating the prolongation of the judicial procedures applies for Hungary as well. In general, it can be concluded that the Hungarian legal system provides the basic human right to fair trial. This claim is supported by the low number of infringements in Hungary. In this study I sought to present the data related to the Hungarian cases proceeding at the European Court of Human Rights, as well as elementswarranting the emergence of the right to a fair trial assured by Article 6, together with the aspects during the monitoring of the cases of the prolongation of the judicial procedures respected by the Court of Strasbourg. Finally I aimed to delineate the aforesaid apropos of a representative and an exceptional case in respect of the practice of the Court as well.